129k views
4 votes
Which equation is the inverse of (x-4)² - 2/3 = 6y-12 ?

User The Hog
by
4.7k points

2 Answers

2 votes

Answer:


x=((y-4)^2)/(6)+(17)/(9)

is the inverse of the function.

Explanation:

We have been given the function:


(x-4)^2-(2)/(3)=6y-12

For inverse function we will swap x and y

And firstly, we will find the value of y in terms of x

and then replace x and y


6y=(x-4)^2-(2)/(3)+12


6y=(3(x-4)^2-1+36)/(3)


y=((x-4)^2)/(6)+(17)/(9)

Now, we will replace x and y


x=((y-4)^2)/(6)+(17)/(9)


User Anthony Roberts
by
6.0k points
5 votes

Answer:


y=\sqrt{6y-(34)/(3)}+4

Explanation:


(x-4)^2-(2)/(3)=6y-12

In order to find the inverse of above function, we solve it for x in term of y and make the replace x with y in the final answer.

Adding \frac{2}{3} on both hand sides we ger


(x-4)^2=6y-12+(2)/(3)\\(x-4)^2=6y+(-36+2)/(3)\\(x-4)^2=6y+(-34)/(3)


(x-4)^2=6y-(34)/(3)

Taking square root on both hand sides we get


(x-4)=\sqrt{6y-(34)/(3)}

Adding 4 on both sides we get


x=\sqrt{6y-(34)/(3)}+4

Replacing x with y and y with x we get


y=\sqrt{6y-(34)/(3)}+4

User Sihoon Kim
by
5.6k points